2018
DOI: 10.3389/fnagi.2018.00384
|View full text |Cite|
|
Sign up to set email alerts
|

Cognitive Profiles and Atrophy Ratings on MRI in Senior Patients With Mild Cognitive Impairment

Abstract: In this cross-sectional study, we sought to describe cognitive and neuroimaging profiles of Memory clinic patients with Mild Cognitive Impairment (MCI). 51 MCI patients and 51 controls, matched on age, sex, and socio-economic status (SES), were assessed with an extensive neuropsychological test battery that included a measure of intelligence (General Ability Index, “GAI,” from WAIS-IV), and structural magnetic resonance imaging (MRI). MCI subtypes were determined after inclusion, and z-scores normalized to our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 81 publications
2
10
0
Order By: Relevance
“…These results are in agreement with a perfusion study that showed significant regional hypoperfusion in patients suffering from MCI compared to the CN group in the parietal lobe [35]. Also in another study, the scores on the working memory domain correlated inversely with the parietal lobe atrophy score in MCI patients [36], which confirms the damage to the parietal lobe in MCI patients, similar to our results.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with a perfusion study that showed significant regional hypoperfusion in patients suffering from MCI compared to the CN group in the parietal lobe [35]. Also in another study, the scores on the working memory domain correlated inversely with the parietal lobe atrophy score in MCI patients [36], which confirms the damage to the parietal lobe in MCI patients, similar to our results.…”
Section: Discussionsupporting
confidence: 93%
“…Its sensitivity and specificity are similar to automated methods measuring volume and cortical thickness volume 26 . In contrast, Korf et al 24 , Flak et al 25 , and Rhodius-Meester et al…”
Section: Discussionmentioning
confidence: 95%
“…In 2017, another study also demonstrated the efficacy of SS as an MCI diagnostic tool 24 . The SS has been shown to correlate significantly with qualitative hippocampal measurements and is of greater clinical relevance when associated with cognitive function 25 . Its sensitivity and specificity are similar to automated methods measuring volume and cortical thickness volume 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The medial temporal lobe is a key anatomical structure of episodic memory, and structural alterations are found in most typical variants of AD, including prodromal AD and early stages of AD ( 28 ). Compared to more complex gray matter (GM) MRI volumetric analyses, the MTA visual rating scale is considered a brief measure that can be applied in daily clinical practice ( 10 , 23 , 29 ). For each age group and cutoff score, the MTA's AUC in our cohort demonstrated good discriminative properties for differentiating prodromal AD from controls with results similar to a cohort from one memory clinic in China ( 30 ), as well as for discriminating controls from AD ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in LAC, the most widely available clinical methods to assess relationships between brain structures and their functions are neuropsychological testing and visual assessments of cortical atrophy patterns on brain MRI imaging by the practitioner ( 8 ). The most widely used MRI visual scoring system is the medial temporal lobe atrophy (MTA) score ( 9 ), which has a high sensitivity for the detection of prodromal AD (or mild cognitive impairment due to AD) and AD ( 10 ). Other MRI visual rating scales validated for use for dementia include the posterior atrophy (PA) scale ( 11 ) and global cortical atrophy-frontal (GCA-F) scale, which may serve as potential biomarkers for atypical AD and non-AD dementias ( 8 ).…”
Section: Introductionmentioning
confidence: 99%